Reproduction of entomopathogenic nematodes of the genera Steinernema Travassos, 1927 (Rhabditida: Steienernematidae) within strawberry blossom weevil larvae Anthonomus rubi Herbst, 1795 (Coleoptera: Curculionidae) - Sigareva, D.; Kharchenko, V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
Studies have been conducted on the contamination in the laboratory of larvae of raspberry-straw weevil (Anthonomus rubi Herbst, 1795) with two isolates of entomopathogenic nematodes (ETNs) of the genus Steinernema Travassos, 1927, vchecked the possibility of their reproduction under these conditions, and features of quantitative performance indicators. On the basis of the obtained data, it was established that, regardless of the type of isolate of the EPN, all experimental A. rubi larvae died on the 3rd day after infection, and the yield of larvae nematodes from the dead insects began on day 10—12 and lasted 42—44 days. During this period, on average, from one of the affected specimens of raspberry-straw weevil, from 26965 to 29168 larvae of the EPN was allocated. The total number of larvae of EPN obtained in the infection of 14 larvae of weevil of raspberry-strawberry was 392929 individuals. The migration of newly-formed individuals of the EPN was uneven, the bulk of the larvae (61—66.2%) is released during the second decade of the month, the rest — 24.5%—31.2% in the third decade. In the first and last decades the larvae are significantly less (3.5—5.8%).